Paciente femenino de 75 años de edad con insuficiencia respiratoria aguda asociada a la neumonía adquirida en la comunidad. - Pino García, Génesis Yudexi (2021)
As a next professional in the health area, I want to contribute with this study to publicize everything related to acute respiratory failure in elderly patients, which is one of the most affected population with this disease and other respiratory diseases. Nowadays, acute respiratory failure is one of the main reasons for consultation in the different hospitals of the country, which is why it is of the utmost importance to publicize everything that comes with suffering from this disease. For a correct diagnosis, the characteristic clinical picture of this pathology must be recognized and in turn carry out complementary tests to make a correct diagnosis. The elderly population today is one of the most affected people with this disease. Acute respiratory failure "ARF" is one of the leading causes of universally infectious death in the world, because the mortality rate of the disease doubles with age and has a high incidence. That is why this work was carried out focused on an 75-year-old male patient, which collects everything related to acute respiratory failure, as well as help the different professionals in the health area to know more everything what is related to this disease and in turn how treatment should be applied in patients with acute respiratory failure.